Achille Mbembe - Coates, Oliver 1984- (Routledge, 2025)
"Achille Mbembe is a key thinker in contemporary African philosophy, who has been influential in literary and cultural theory, African literature, and postcolonial studies. Oliver Coates introduces key concepts within Mbembe's thought in relation to African history, literature, and philosophy. This accessible guide: - Considers examples from African literature in Arabic, English, French, and Yoruba, and shows the relevance of Mbembe's thought beyond Anglophone writing; - Explores how Mbembe's work relates to contemporary global events, and charts Mbembe's intellectual development between Cameroon, France, and the U.S.A.; - Discusses core concepts from across Mbembe's career, including the positioning of Africa within Western and Afrodiasporic thought, the colony, postcolony, necropolitics, decolonization, Afropolitanism, technology, and the environment; - Reveals Mbembe's engagement with key global events including the #RhodesMustFall and #BlackLivesMatter movements, and the call for the restitution of African objects in Western museums. Offering a clear and accessible route into what can be a complex area, this book shows the significance of Mbembe's thought across literature, history, postcolonial studies, gender studies and critical theory"--
Includes bibliographical references and index
2412
Keywords: Mbembe, Achille / 1957-; Philosophers / Africa / Biography; Historians / Africa / Biography; Philosophy, African; Postcolonialism